S1PR-1/5 modulator RP-101074 shows beneficial effects in a model of central nervous system degeneration - Sindi, Mustafa; Hecker, Christina; Issberner, Andrea; Ruck, Tobias; Meuth, Sven G.; Albrecht, Philipp; Dietrich, Michael (Frontiers in Immunology, 2023)
In multiple sclerosis (MS), chronic disability primarily stems from axonal and neuronal degeneration, a condition resistant to conventional immunosuppressive or immunomodulatory treatments. Recent research has indicated that selective sphingosine-1-phosphate receptor S1PR-1 and -5 modulators yield positive effects in progressive MS and mechanistic models of inflammation-driven neurodegeneration and demyelination. In this study, the S1PR-1/-5 modulator RP-101074 was evaluated as a surrogate for ozanimod in the non-inflammatory, primary degenerative animal model of light-induced photoreceptor loss (LI-PRL) in CX3CR1-GFP mice to assess potential neuroprotective effects, independent of its immunomodulatory mechanism of action. Prophylactic administration of RP-101074 demonstrated protective effects in the preclinical, non-inflammatory LI-PRL animal model, following a bell-shaped dose-response curve. RP-101074 treatment also revealed activity-modulating effects on myeloid cells, specifically, CX3CR1+ cells, significantly reducing the marked infiltration occurring one week post-irradiation. Treatment with RP-101074 produced beneficial outcomes on both retinal layer thickness and visual function as evidenced by optical coherence tomography (OCT) and optomotor response (OMR) measurements, respectively. Additionally, the myelination status and the quantity of neural stem cells in the optic nerve suggest that RP-101074 may play a role in the activation and/or recruitment of neural stem cells and oligodendrocyte progenitor cells, respectively.